(untitled) ("Temas Sociais" Journal, 2021)
In this article, we intend to reflect on Social Work in Portugal, more specifically on Graduated Training given in Social Work, using therefore a socio-historical analysis of the profession in Portugal, in order to reflect on the path taken until today, as well as the impact that the various political social transformations had and have in the formation in Social Work. The reflection developed favors training as a structuring and identity element of the profession. Reflecting on Social Work as well as on its contribution to society, becomes an uninterrupted exercise, especially in an era in which social rights are overtaken by neoliberal impositions and marked by the retraction of state responsibility, implying that the social worker is the holder of critical, reflective and political thinking.